Using ecological niche modeling to model invasion risk of hornets (Hymenoptera: Vespidae) in Iran - Ehsan Rahimi; Chuleui Jung (Journal of Ecology and Environment)
Background: Among the 22 species in the Vespa genus, five have successfully established populations outside their native ranges, while four others have been recorded either in natural habitats or during border inspections in various countries. This study aims to assess the potential threat posed by 12 hornet species-Vespa crabro, Vespa mandarinia, Vespa simillima, Vespa velutina, Vespa affinis, Vespa analis, Vespa basalis, Vespa bicolor, Vespa ducalis, Vespa dybowskii, Vespa soror, and Vespa tropica-within the geographical and ecological context of Iran, an arid Middle Eastern country. Using ecological niche modeling, we analyzed species occurrence data alongside climatic variables with minimal correlation to predict the potential distribution of these hornets across Iran. The mobility-oriented parity method was applied to identify areas where strict extrapolation is relevant for these species. Additionally, we generated a habitat suitability map for Apis mellifera (honey bee) using ecological niche modeling and compared the spatial overlap between the predicted risk maps for the hornets and the honey bee habitat suitability map, employing Schoener's D metric. Results: The results revealed two key findings. First, a significant portion of Iran exhibits climatic dissimilarity compared to the native habitats of certain hornet species. Second, the spatial overlap analysis showed varying degrees of overlap between A. mellifera habitats and the potential distributions of different hornet species. Notably, V. mandarinia and V. crabro demonstrated the highest overlap values (D = 0.68), suggesting that these hornets could share substantial habitat preferences or ecological roles with honey bees in Iran. Conclusions: Although most regions of Iran appear less suitable for hornet invasions, caution is warranted in the northern areas, where trade and exchanges could serve as pathways for Vespa hornet introductions. These findings highlight the importance of targeted monitoring and preventative measures in these high-risk regions.